2022
DOI: 10.1111/mpp.13223
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors VaERF16 and VaMYB306 interact to enhance resistance of grapevine to Botrytis cinerea infection

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…In Lilium longiflorum , the heat-inducible LlERF110 may hinder the establishment of thermotolerance via being recruited to GCC-elements ( Li T. et al., 2022 ). Zhu et al. (2022) suggested that VaERF16 from Chinese wild grape ( Vitis.…”
Section: Erfs Of Different Subgroup Selectively Bind To Particular Ci...mentioning
confidence: 99%
See 2 more Smart Citations
“…In Lilium longiflorum , the heat-inducible LlERF110 may hinder the establishment of thermotolerance via being recruited to GCC-elements ( Li T. et al., 2022 ). Zhu et al. (2022) suggested that VaERF16 from Chinese wild grape ( Vitis.…”
Section: Erfs Of Different Subgroup Selectively Bind To Particular Ci...mentioning
confidence: 99%
“…On the other hand, it was found that protein-protein interactions between ERF and WRKY and synergistic regulatory effects in Arabidopsis and Persimmons ( Diospyros kaki Thunb) ( Zhu et al., 2019 ). In addition, Zhu et al. (2022) demonstrated that VaERF16 from Vitis amurensis ‘Shuang You’ interacted with the MYB family transcription factor VaMYB306, and the VaERF16-VaMYB306 transcriptional complex resulted in higher transcript levels of VaPDF1.2 to enhance resistance of grapevine to Botrytis cinerea infection.…”
Section: Regulatory Mechanism Of Erfs Involved In Their Transcription...mentioning
confidence: 99%
See 1 more Smart Citation
“…Well-watered plants were used as the positive control plants. For Pst.DC3000 infection was performed as described by Zhu et al (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Until now, there were no QTL mapping reports related to grape gray mold resistance, and research on gray mold resistance transcriptional regulation mechanism was majorly focused on the transcription factor ERF and MYB families in Arabidopsis and tomato ( Lorenzo et al., 2003 ; Pre et al., 2008 ; Zhao et al., 2012 ; Liu et al., 2021 ). In grapevine, there have been some reports related to gray mold resistance including structure genes VvSWEE4 , VvSWEE15 , VvSWEET7 , and VvAMP2 and some transcription factors including VvWRKY52 , VqERF072 , VqERF112 , VqERF114 , VaERF20 , VaERF16 , and VaMYB306 ( Nanni et al., 2014 ; Jiao et al., 2015 ; Wang et al., 2018a ; Wang et al., 2018b ; Breia et al., 2019 ; Zhu et al., 2019 ; Wang et al., 2020 ; Zhu et al., 2022 ). While the quantitative trait was controlled by many genes, candidate genes related to gray mold resistance in grapevine still need to be explored.…”
Section: Introductionmentioning
confidence: 99%